R(3,4)=17 - Prałat, Paweł (The Electronic Journal of Combinatorics, 2008)
In this paper, we consider the on-line Ramsey numbers R (k,l) for cliques. Using a high performance computing networks, we ’calculated’ that R(3,4)=17. We also present an upper bound of R(k,l), study its asymptotic behaviour, and state some open problems.